Degradation of leaves and cellulose by Bacillus subtilis CL3 and Pseudomonas aeruginosa CL5 isolated from left waste dumps in Vietnam - Duc, Ha Danh (Academia Journal of Biology, 2018)
The biodegradation capacity of two bacterial strains, Bacillus subtilis CL3 and Pseudomonas aeruginosa CL5, isolated from left waste dumps on thee different plant leaves were investigated. The leaves were derived from perennial plants, Malabar almond tree (Terminalia catappa), eucalyptus (Eucalyptus terticornis) and African mahogany (Khaya senegalensis). Among those 3 plants, Eucalyptus terticornis is known to be resistant for biodegradation in nature. In our study, B. subtilis CL3 could degrade a half of Eucalyptus terticornis leaves within 10 days. On the other hand, P. aeruginosa CL5 showed relatively poor degradation rate of the leaves of Eucalyptus terticornis, but could effectively degrade Khaya senegalensis and Terminalia catappa leaves than B. subtilis CL3. When these two bacteria strains were mixed, the degradation rates of all these types of leaves were enhanced. While B. subtilis CL3 could utilize 1,8-cineole, a component extracted from Eucalyptus terticornis, as a sole carbon source, this component inhibited the growth of P. aeruginosa CL5. The multiple and efficient left degradation capacities make these isolates good candidates for bioremediation of leaf waste and cellulose. Citation: Ha Danh Duc, 2017. Degradation of leaves and cellulose by Bacillus subtilis CL3 and Pseudomonas aeruginosa CL5 isolated from left waste dumps in Vietnam. Tap chi Sinh hoc, 39(4): 483-488. DOI: 10.15625/0866-7160/v39n4.10744.*Corresponding author: hadanhduc@gmail.comReceived 5 December 2016, accepted 12 December 2017